2022
DOI: 10.3390/ani12101296
|View full text |Cite
|
Sign up to set email alerts
|

Microbiota Composition of Mucosa and Interactions between the Microbes of the Different Gut Segments Could Be a Factor to Modulate the Growth Rate of Broiler Chickens

Abstract: The study reported here aimed to determine whether correlations can be found between the intestinal segment-related microbiota composition and the different growing intensities of broiler chickens. The bacterial community structures of three intestinal segments (jejunum chymus—JC, jejunum mucosa—JM, caecum chymus—CC) from broiler chickens with low body weight (LBW) and high body weight (HBW) were investigated. Similar to the previous results in most cases, significant differences were found in the bacteriota d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 70 publications
2
19
0
Order By: Relevance
“…Actinobacteria and Lactobacillus showed critical roles in weight gain, and they were shown to be considerably higher with increasing weight gain. Similar to our findings reported by Farkas et al, [ 13 ], who stated that the co-occurrence interaction results in the jejunum revealed a correlation between the genera of Actinobacteria and Firmicutes Bacilli classes with different patterns in the two BW groups. Actinobacteria are the highest producers of bioactive secondary metabolites and can be used as a probiotic candidate, particularly in the poultry industry [ 53 ].…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Actinobacteria and Lactobacillus showed critical roles in weight gain, and they were shown to be considerably higher with increasing weight gain. Similar to our findings reported by Farkas et al, [ 13 ], who stated that the co-occurrence interaction results in the jejunum revealed a correlation between the genera of Actinobacteria and Firmicutes Bacilli classes with different patterns in the two BW groups. Actinobacteria are the highest producers of bioactive secondary metabolites and can be used as a probiotic candidate, particularly in the poultry industry [ 53 ].…”
Section: Discussionsupporting
confidence: 92%
“…Our results are similar to those of Liu et al [ 45 ], who also failed to detect differences in the diversity of the ileum and cecal microbial community between chickens with different feed efficiencies [ 45 ]. In a recent comparison between the microbiota composition in two body weight groups of a commercial line (i.e., Ross), no significant differences were found in the alpha diversity at the jejunum contents—JC, jejunum mucosa—JM, and caecum contents—CC places, but β-diversities showed considerable separation between the JC, JM, and CC [ 13 ]. In our study, similar results were found, which suggested that the gut microbiota within the studied chicken was identical and exhibited limited diversity [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Bilophila was associated with obesity in mice induced by a high-fat diet ( 41 ), but it was also found to be significantly negatively correlated with broiler weight ( 42 ). As a potential beneficial bacterium, Akkermansia was more abundant in the better-fed efficacy group hens ( 43 ).…”
Section: Discussionmentioning
confidence: 99%